Reaching new heights: 20 years of nutrition progress in Nepal - Cunningham, Kenda; Singh, Akriti; Headey, Derek D.; Pandey Rana, Pooja; Karmacharya, Chandni (International Food Policy Research Institute, 2016)
DESPITE SIGNIFICANT ECONOMIC growth, South Asia remains notorious for its alarmingly high rates of undernutrition. This “Asian enigma” has long puzzled both researchers and policymakers. However, Nepal’s recent experience presents yet another enigma: a rapid reduction in maternal and child undernutrition during a period of civil war and prolonged political and economic instability. From 1996 to 2011, the prevalence of stunting among children under two years of age fell from 48 to 27 percent, and the prevalence of maternal underweight decreased from 28 to 20 percent.